Investigation of Students' Teaching Assistant Abilities in the Accuracy of Assessment Selection for Movement Skill Elements in Physical Education Learning - Nadiyah, Rany Ade Akhsanu; Fitriady, Gema (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2024)
This study aims to describe the accuracy of the selection of 2020 PJKR students from State University of Malang who participated in the Teaching Assistance Program in the preparation of teaching modules or lesson plans. This research method is carried out with a qualitative and quantitative form survey model. The subjects of this study were all undergraduate students of Physical Education Health and Recreation who participated in the Teaching Assistance Program in the odd semester of 2023-2024 as many as 123 students. However, only 98 students were willing to become research subjects while 25 other students did not fill out the willingness to participate in the research form. Data were collected using documentation and interview techniques. The results showed that 96% of students were still not correct or appropriate in choosing the assessment of movement skill elements based on the level of difficulty and material. This can be used as a benchmark by lecturers to plan evaluation and guidance during or before the implementation of the internship program, especially teaching assistance so as to minimize existing errors, especially in the selection of assessments based on the level of difficulty and material.